Rocket Puppies - Joyce, William (2024)
In a world overcome by sadness, the arrival of Rocket Puppies from the outer reaches of Not-from-Here brings joy and laughter, but the puppies must face off against Snarly McBummerpants and stop him from spreading gloom with Mopey Smoke.
"A Caitlyn Dlouhy Book."
Keywords: Dogs -- Fiction; Animal infancy -- Fiction; Superheroes -- Fiction; Emotions -- Fiction